Investigating Non-Linguistic Problems Faced by the Students in Speaking English - Fitri, Mainar; Murny, Murny; Nurzena, Nurzena (Gurindam: Jurnal Bahasa dan Sastra, 2024)
Linguistic problems were found as problems faced by students in speaking English. This research aimed to describe students’ non-linguistic problems in speaking English. It was descriptive quantitative research. The data were collected by using questionnaires, and analyzed by using percentage. The result of the research showed that the percentage of students’ non-linguistic problem in speaking English were inhibition (25.6%), Nothing to say (25.2%), Low Participant (25.1%), and Mother-Tongue (24.1%). It can be concluded that inhibition was the dominant non-linguistic problem students faced in speaking English.Keywords: investigating, non-Linguistic problems, speaking English.